Pengaruh Citra Merek Terhadap Pengambilan Keputusan Pembelian Teh Botol Sosro - Azis, Fahmi Rizal Abdul; Fitriadi, Budhi Wahyu; Umbara, Dona Setia (Cangkok, 2023)
Brand image is one of teh key factors in influencing consumer buying behavior, especially in teh packaged beverage industry. Teh sosro bottle is one of teh most popular brands of teh saji in Indonesia. This study aims to analyze teh influence of brand image on teh purchase decision of teh sosro bottle. Teh method used is quantitative descriptive. Teh sample used was 80 respondents of teh Faculty of Agriculture, University of Struggle Tasikmalaya. Data was collected through questionnaires that focused on consumer perceptions regarding teh brand image of teh sosro bottle. Teh results showed that as many as 29 respondents (36%) viewed teh brand image of Teh botol sosro as very good. A total of 48 respondents (60%) have a good category in making purchasing decisions for sosro bottled tea. And brand image has a significant influence on teh purchase decision making of Teh Botol Soro.